Raynaud Phenomenon: Diagnosis and Management - Fitriani Fitriani; Citra Tresna Murti; Soenarto K (HM Publisher, 2020)
Raynaud’s phenomenon (RP) is a chronic episodic attack of digital ischemia provoked by exposure to cold or emotional stres. This phenomenon affects 3-5% of the population, with female ratio more than men and is categorized into a primary and secondary form. Primary form of RP is idiopathic, meanwhile the secondary form is associated with underlying diseases and other condition such as connective tissue disease, obstructive arterial disease, neurologic disorders, drugs and toxin, hyperviscosity disorders, infections, endocrine disturbance, neoplasms, and occupation or environmental exposure. Until today, to classified and build the diagnosis of RP is still a clinical challenge. Therefore, a careful history and a physical examination, together with laboratory tests and nailfold capillaroscopy are mandatory. A combination of conservative measures and medications can help in the management of RP. The approach to the RP patients requires therefore a coordinated care of specialists including dermatology.